2007
DOI: 10.1136/bjsm.2006.032334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a maximal exercise test on neurocognitive function

Abstract: Objective: To examine the effects of a maximal exercise test on cognitive function in recreational athletes. Design: A repeated-measures design was used to compare baseline with post-cognitive function and fatigue symptoms after a maximal exercise test. Setting: Division 1 American Midwestern University, (Michigan State University, Michigan, USA). Participants: 102 male and female recreational athletes. Intervention: Participants in the experimental group (n = 54) were asked to perform a maximal treadmill exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 17 publications
4
58
4
1
Order By: Relevance
“…Participants completed the ImPACT test in approximately 25-40 min. All testing was conducted at a designated time prior to the final practice of the season, to avoid potential exertion effects on computerized neurocognitive testing reported in the literature [33]. Prior to collecting the ImPACT and symptom data, the researchers recorded heading data for each player at two randomly selected practices and games to determine heading exposures per practice and game for each player.…”
Section: Methodsmentioning
confidence: 99%
“…Participants completed the ImPACT test in approximately 25-40 min. All testing was conducted at a designated time prior to the final practice of the season, to avoid potential exertion effects on computerized neurocognitive testing reported in the literature [33]. Prior to collecting the ImPACT and symptom data, the researchers recorded heading data for each player at two randomly selected practices and games to determine heading exposures per practice and game for each player.…”
Section: Methodsmentioning
confidence: 99%
“…It is challenging to set a cut-off score following a period of physical exertion, whether it is game related or part of an exercise provocation protocol, as Symptom Scores can be significantly influenced by the intensity and fatiguing effects of exercise 77 89. This can be addressed by the development of a standardised exercise protocol which models the internationally recommended RTP protocol.…”
Section: Moving Towards An Operational Definition Of 'Asymptomatic' Imentioning
confidence: 99%
“…This is important, because the literature has identified that alertness at the time of testing, intensity of exercise, and sport may have an effect on testing. 5,11 Although the authors attempted to have testing performed at a similar time and under similar testing conditions, none of the variables were controlled for and need to be acknowledged as such. Fourth, our study did not utilize a control group, which might have limited the significance of the findings.…”
Section: Discussion Ementioning
confidence: 99%